Assessing Language and Literacy with Bilingual Students : Practices to Support English Learners. - Helman, Lori (Guilford Publications, 2019)
"From expert authors, this book guides educators to conduct assessments that inform daily instruction and identify the assets that emergent bilinguals bring to the classroom. Effective practices are reviewed for screening, assessment, and progress monitoring in the areas of oral language, beginning reading skills, vocabulary and comprehension in the content areas, and writing. The book also addresses how to establish schoolwide systems of support that incorporate family and community engagement. Packed with practical ideas and vignettes, the book focuses on grades K-6, but also will be useful to middle and high school teachers. Appendices include reproducible forms that can be downloaded and printed in a convenient 8 1/2" x 11" size"-- Provided by publisher.
Keywords: Education, Bilingual -- Study and teaching.; Second language acquisition -- Study and teaching.; Langue seconde -- Acquisition -- Étude et enseignement.; Education, Bilingual -- Study and teaching; Second language acquisition -- Study and teaching